A Case Study on Design of Ring Footing for Oil Storage Steel Tank. - M. AshourAl.Khuzaie, Hussein; Jabbar Abbas, Basim (International Journal of Engineering and Technology, 2018)
Foundations of large steel oil storage tanks considered as case study to conduct the correct steps of the foundation design. This study aims at understanding the principles of the geotechnical and structural design of foundation for heavy oil storage steel tank. The storage tank is used in the Iraqi oil industry at Basra, south of Iraq. The steel tank 26.78 m in diameter and 10 m height and the transmitted load is in pattern of a line load along the circumference of tank. A finite element model using SAP program was using to simulate the foundation as a ring footing. Two series of long driven piles were used along the circumference of tank to support the applied load from the tank and oil liquid and to be as a base of the ring beam reinforced concrete beam.Â Â